Difficulty Emotion Regulation as a Predictor of Adolescent Depressive Symptoms - Rodhiyah, Isyah; Djuwita, Efriyani (Psikostudia : Jurnal Psikologi, 2023)
In adolescence many psychological problems develop and manifest for the first time, e.g depressive symptoms. Depressive symptoms refer to an unhappy mood, feeling gloomy, sad, and indecisive. Depressive symptoms are related to adolescents' difficulties in regulating emotions. Someone with poor emotional regulation tends to have difficulty dealing with negative emotions from the stress they experience which then has the potential to increase depressive symptoms. This study aims to examine the difficulties of emotion regulation as a predictor of depressive symptoms in adolescents. The research was conducted using a quantitative method with a cross-sectional design and a correlational research type. The participants were 446 adolescents aged 13-17 years, who were obtained by convenience sampling technique. Difficulties of the Emotion Regulation Scale (DERS) and Short Mood and Feelings Questionnaire (SMFQ) were used as instrument in this study. The results show that difficulties in emotion regulation predicts depressive symptoms in adolescents. In more detail, the dimensions of lack of awareness, lack of clarity, nonacceptable emotional responses, and limited emotion regulation strategies predict depressive symptoms in adolescents. This happens because the lack of awareness, clarity, and limited emotion regulation strategies makes individuals use maladaptive strategies so that adolescents have depressive symptoms. In addition, nonacceptance emotions response makes adolescents feel higher negative affect. Based on these results, it is important for adolescents to get interventions to overcome difficulties in emotion regulation so that they are not prone to experiencing depressive symptoms.Pada masa remaja banyak masalah psikologis berkembang dan bermanifestasi untuk pertama kalinya, salah satunya gejala depresi. Gejala depresi mengacu pada suasana hati yang tidak bahagia, perasaan suram, sedih dan bimbang. Gejala depresi erat kaitannya dengan kesulitan remaja dalam meregulasi emosinya. Seseorang dengan regulasi emosi yang buruk cenderung kesulitan untuk mengatasi emosi negatif dari stress yang mereka alami yang kemudian berpotensi terhadap peningkatan gejala depresi. Penelitian ini bertujuan melihat kesulitan regulasi emosi sebagai prediktor gejala depresi yang dialami remaja. Penelitian dilakukan dengan metode kuantitatif dengan desain cross-sectional dan tipe penelitian korelasional. Partisipan penelitian terdiri atas 446 remaja berusia 13-17 tahun, yang didapatkan dengan Teknik convenience sampling. Difficulties Emotion Regulation Scale (DERS) dan Short Mood and Feelings Questionnaire (SMFQ) yang telah diadaptasi ke dalam Bahasa Indonesia digunakan dalam penelitian ini. Hasil menunjukkan kesulitan regulasi emosi memprediksi gejala depresi pada remaja. Secara lebih detil, dimensi lack of awareness, lack of clarity, nonacceptance emotional response, dan limited of regulation emotion strategies yang memprediksi gejala depresi pada remaja. Hal ini terjadi karena kurangnya kesadaran, kejernihan, dan terbatasnya penggunaan strategi regulasi emosi membuat individu menggunakan strategi yang maldaptif sehingga remaja memiliki gejala depresi. Selain itu, penolakan terhadap emosi membuat remaja merasakan afek negatif yang lebih tinggi. Berdasarkan hasil ini, penting bagi remaja mendapatkan intervensi untuk mengatasi kesulitan dalam regulasi emosi sehingga tidak rentan mengalami gejala depresi.